The Influence of Knowladge and Atitudes on the Implementation of End of Life Care among Nurses in the Emergency Room and Intensive Room - Alvareza Ratih Damayanti, Anastasia; Koerniawan, Dheni; Frisca, Sanny (UKMC International Conference (UKMC IC) Proceedings, 2024)
fff